Simulants of malignant melanoma - Gérald E. Piérard; Claudine Piérard-Franchimont; Philippe Delvenne (Frontiers Media S.A., 2015)
During the recent period, dermoscopy has yielded improvement in the early disclosure of various atypical melanocytic neoplasms (AMN) of the skin. Beyond this clinical procedure, AMN histopathology remains mandatory for establishing their precise diagnosis. Of note, panels of experts in AMN merely report moderate agreement in various puzzling cases. Divergences in opinion and misdiagnosis are likely increased when histopathological criteria are not fine-tuned and when facing a diversity of AMN types. Furthermore, some AMN have been differently named in the literature including atypical Spitz tumor, metastasizing Spitz tumor, borderline and intermediate melanocytic tumor, malignant Spitz nevus, pigmented epithelioid melanocytoma or animal-type melanoma. Some acronyms have been further suggested such as MELTUMP (after melanocytic tumor of uncertain malignant potential) and STUMP (after Spitzoid melanocytic tumor of uncertain malignant potential). In this review, such AMN at the exclusion of cutaneous malignant melanoma (MM) variants, are grouped under the tentative broad heading skin melanocytoma. Such set of AMN frequently follows an indolent course, although they exhibit atypical and sometimes worrisome patterns or cytological atypia. Rare cases of skin melanocytomas progress to loco regional clusters of lesions (agminate melanocytomas), and even to regional lymph nodes. At times, the distinction between a skin melanocytoma and MM remains puzzling. However, multipronged immunohistochemistry and emerging molecular biology help profiling any malignancy risk if present.